The Effect of Spiritual Guidance of Reproductive Health by Booklets on The Changes of Adolescent's sAttitudes: Dating Status In Premarital Sexual Behavior - Sitawati Sitawati; Suriah Suriah; Saidah Syamsuddin; Sutinah Made; Werna Nontji; Muhammad Tamar (Poltekkes Kemenkes Palu, 2021)
The spiritual guidance of reproductive health and safety is oriented towards strengthening moral ​​and religious values ​​in addressing adolescent reproductive health problems with an approach on several aspects, such as preventive, curative, rehabilitative, and developmental. The booklet is a medium of guidance/learning that can attract interest and help teenagers understand the guidance material. This study aimed to determine the effect of the spiritual guidance of reproductive health care professionals by booklets on changes in adolescent attitudes towards dating status in premarital sexual behavior. A combination of qualitative and quantitative experimental research with a pre-experimental design, one group pretest-posttest, with a total sample of 26 adolescents, selected a purposive sampling technique. The spiritual guidance intervention used booklets for six meetings with 60-90 minutes each meeting within 2 months. Data were collected through pre-test and post-tests using interview sheets and Likert scale questionnaires. Data were analyzed qualitatively and statistically tests using the Wilcoxon test. The results showed that the sexual behavior of adolescents in dating was including holding hands, embracing the arms/shoulders and waist, hugging, kissing cheeks and lips, stroking the head, laying on the partner's thighs, and having sex with condoms. Then, from the statistical test, the negative ranks between the pre-test and post-test values were 0. Meanwhile, the positive ranks between the pre-test and post-test values indicated that 24 respondents with a positive value and a mean rank value of 13.00, and 2 respondents with a pre-post value remain the same. The Wilcoxon test shows the p-value (sig) 0.000 <0.05. Thus, the spiritual guidance of reproductive health care professionals using booklets significantly affected changes in adolescent attitudes towards dating status in premarital sexual behavior.